Towards a performative understanding of deservingness: Merit, gender and the BBC pay dispute. Issue 2 (30th July 2019) - Simpson, Ruth; Kumra, Savita; Lewis, Patricia; Rumens, Nick
Abstract : Drawing largely on a high‐profile case of unequal pay at the BBC (British Broadcasting Corporation) as an illustrative example, this conceptual article considers differences and interrelationships between merit and deservingness, where the latter captures how, through appropriate performances, merit is given recognition and value. We propose a performative understanding of deservingness that highlights its gendered and embodied dimensions. Informed by Judith Butler's account of gender performativity, we show that, while merit is conventionally conceptualized as a relatively fixed set of attributes (qualifications, skill) 'attached' to the individual, deservingness captures how, in gendered terms, value and recognition are both claimed and conferred. As we argue, a gendered, deserving subject does not pre‐exist but is performatively constituted through embodied practices and performances of what is seen as worthy in a particular time and place.